2019
DOI: 10.3390/c5030043
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Activated Carbon Based on Deep Eutectic Solvents (DES) and H3PO4

Abstract: In this present work, a novel method for synthesis of palm kernel shell activated carbon was established using DES (choline chloride/urea)/H3PO4 as the activating agent. The pore characterization, morphology, and adsorption properties of the activated carbons were investigated. The activated carbon samples made from the same feedstock at two pyrolysis temperatures (500 and 600 °C) were compared for their ability to adsorb Pb(II) in aqueous solution. The results demonstrated that the production of the activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The average of 30.96% of char obtained in this work produced from the PKS consists of 20.8-27.7% cellulose, 21.6-22.3% hemicelluloses, and 44.0-50.7% lignin [56,73]. Previous studies affirmed that cellulose, hemicellulose, and lignin are the most abundant components of crude biomass materials, including PKS [7,22,55,58]. The studies postulated that the composition of biomass influences the derived carbonaceous material properties, and hence show the possible transformation of cellulose, hemicelluloses, and lignin to graphitic materials by the dehydration condensation process.…”
Section: Measurement Of Quantum Yieldssupporting
confidence: 50%
See 1 more Smart Citation
“…The average of 30.96% of char obtained in this work produced from the PKS consists of 20.8-27.7% cellulose, 21.6-22.3% hemicelluloses, and 44.0-50.7% lignin [56,73]. Previous studies affirmed that cellulose, hemicellulose, and lignin are the most abundant components of crude biomass materials, including PKS [7,22,55,58]. The studies postulated that the composition of biomass influences the derived carbonaceous material properties, and hence show the possible transformation of cellulose, hemicelluloses, and lignin to graphitic materials by the dehydration condensation process.…”
Section: Measurement Of Quantum Yieldssupporting
confidence: 50%
“…The dehydration condensation process is one way to form carbonaceous materials or CDs when biomass, precisely, cellulose, hemicellulose, and lignin subjected to pyrolysis. The authors showed that the individual percentage conversion of the constituents of biomass was as follows: cellulose (9%), hemicellulose (0%), and lignin (39%) at 900 • C and 21%, 4.6% and 52% at 400 • C calcination temperature, respectively [7,22,55,58]. Jiang et al and Nasir et al have characterized the graphitic material obtained from the char of carbonized PKS to graphene oxide and reduced graphene oxide.…”
Section: Measurement Of Quantum Yieldsmentioning
confidence: 99%
“…Their findings indicated that the pharmaceutical compounds have a low level of adsorption abilities in the activated carbon. Aloysius [15] used activated carbon samples at two pyrolysis temperatures and evaluated their adsorption capacity in aqueous solution. Research results showed that activated carbon adsorptive properties were influenced to a great extent by the pyrolysis temperature.…”
Section: Activated Carbonmentioning
confidence: 99%
“…It is observed that DES 1 and DES 3 exist in heterogeneous phase containing liquid and crystalline solid, whereas DES 2 and DES 4 exist in homogeneous liquid phase. Theoretically, DES with good HBA:HBD molar ratio should be clear, transparent liquid without any crystalline solids at room temperature [27]. Only DES 2 and DES 4 fulfil this criterion, which justified that they are successfully synthesized.…”
Section: Selection Of Des For Adsorption Studymentioning
confidence: 98%
“…Since DES 1 and DES 3 were poorly formed, they would not be further investigated in this study. Another criterion of a good DES is to have low viscosity [27]. Table S3 shows the viscosity of DES 2 and DES 4 at various temperatures.…”
Section: Selection Of Des For Adsorption Studymentioning
confidence: 99%